Timing of Tracheostomy in ICU Patients: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Raffaele Merola; Carmine Iacovazzo; Stefania Troise; Annachiara Marra; Antonella Formichella; Giuseppe Servillo; Maria Vargas (Life, 2024)
Background: The ideal timing for tracheostomy in critically ill patients is still debated. This systematic review and meta-analysis examined whether early tracheostomy improves clinical outcomes compared to late tracheostomy or prolonged intubation in critically ill patients on mechanical ventilation. Methods: We conducted a comprehensive search of randomized controlled trials (RCTs) assessing the risk of clinical outcomes in intensive care unit (ICU) patients who underwent early (within 7–10 days of intubation) versus late tracheostomy or prolonged intubation. Databases searched included PubMed, Embase, and the Cochrane Library up to June 2023. The primary outcome evaluated was mortality, while secondary outcomes included the incidence of ventilator-associated pneumonia (VAP), ICU length of stay, and duration of mechanical ventilation. No language restriction was applied. Eligible studies were RCTs comparing early to late tracheostomy or prolonged intubation in critically ill patients that reported on mortality. The risk of bias was evaluated using the Cochrane Risk of Bias Tool for RCTs, and evidence certainty was assessed via the GRADE approach. Results: This systematic review and meta-analysis included 19 RCTs, covering 3586 critically ill patients. Early tracheostomy modestly decreased mortality compared to the control (RR −0.1511 [95% CI: −0.2951 to −0.0070], p = 0.0398). It also reduced ICU length of stay (SMD −0.6237 [95% CI: −0.9526 to −0.2948], p = 0.0002) and the duration of mechanical ventilation compared to late tracheostomy (SMD −0.3887 [95% CI: −0.7726 to −0.0048], p = 0.0472). However, early tracheostomy did not significantly reduce the duration of mechanical ventilation compared to prolonged intubation (SMD −0.1192 [95% CI: −0.2986 to 0.0601], p = 0.1927) or affect VAP incidence (RR −0.0986 [95% CI: −0.2272 to 0.0299], p = 0.1327). Trial sequential analysis (TSA) for each outcome indicated that additional trials are needed for conclusive evidence. Conclusions: Early tracheostomy appears to offer some benefits across all considered clinical outcomes when compared to late tracheostomy and prolonged intubation.